Case Report: Self-Resolved Macular Edema Secondary to Congenital Retinal Macrovessels - Zheng, Fang; Lai, Kairan; Yin, Houfa; He, Jingliang; Xu, Yufeng; Ye, Panpan (Frontiers in Medicine, 2022)
Purpose: To report a case of macular edema secondary to congenital retinal macrovessels (CRM), which resolved spontaneously without any treatment. Observations: A 39-year-old female presented with blurry vision of the right eye for one day. Fundus examination revealed a branch of artery and vein of the inferior retinal arcade crossing the horizontal raphe. Optical coherence tomography (OCT) through the fovea showed cystoid macular edema in the outer plexiform layer. However, no leakage of the vessels was noticed by fundus fluorescein angiography (FFA). Observation was recommended with close follow-up. Two weeks later, the patient returned with good visual acuity, and the macular edema was resolved spontaneously. Conclusions: Macular edema is a possible complication of CRM by increasing retinal capillary hydrostatic pressure. Treatment is not necessary for this kind of macular edema if no leakage of the vessels is noticed on FFA.